Childhood neighborhoods and health: Census-based neighborhood measures versus residential lived experiences. (November 2022) - Roche, Sarah; Spring, Amy; Moore, Alexus
Abstract: This study examines the impact of neighborhood disadvantage and neighborhood social connectedness during childhood on subsequent health status during early adulthood. We link longitudinal data from the Panel Study of Income Dynamics with Census data on children's surrounding neighborhoods. We estimate results with conventional linear regression and novel methods that better adjust for neighborhood selection processes. We find that neighborhood connectedness in childhood is protective against psychological distress in early adulthood, net of selection effects. However, greater connectedness exacerbates the risk of obesity within disadvantaged contexts for Black youth. Our results highlight a potential pathway for improving population health by investing in the social connectedness of neighborhoods alongside reducing structural inequalities. Highlights: Our study utilized novel statistical methods to better account for neighborhood selection. Neighborhood connectedness in childhood is protective against psychological distress in early adulthood. We found no neighborhood effect on the health of White individuals after adjusting for self-selection into neighborhoods. Social connectedness was most detrimental for obesity within the context of structural disadvantage.